Pengaruh Kualitas Pelayanan Account Representative (Ar) Terhadap Kepuasan Dan Kepatuhan Wajib Pajak Badan (Studi Pada Perusahaan Makanan Di Kota Malang) - Pertiwi, Ajeng Rachma; Rusydi, M. Khoiru (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractThe objective of this research is to know influence between account representative quality service as an evidence of administration modernization of taxation with the taxpayer satisfaction and the taxpayer compliance. Quality of service was measured based on tangibles, reliability, responsivness, assurance, and empathy responder. Method applied for data analysis used multiple regression analysis. Analysis result of regression model I indicated tangibles, reliability, responsivness, assurance, and empathy variables had no a significant influence to satisfaction of taxpayer. While partially regression model II indicated that tangibles, reliability, responsivness, and empathy variables didnt have significant effect to taxpayer compliance, and assurance variable has an significant effect to taxpayer compliance. This thing means that taxpayer compliance was influenced by assurance variable. If satisfaction and compliance of taxpayer increased, receiving of tax will increase.